2021
DOI: 10.1016/j.lana.2021.100016
|View full text |Cite
|
Sign up to set email alerts
|

Mean blood pressure according to the hypertension care cascade: Analysis of six national health surveys in Peru

Abstract: Background While we have good evidence about the hypertension care cascade, we do not know the mean blood pressure (BP) in these groups. We described the mean BP in four groups based on the hypertension care cascade at the national and sub-national levels in Peru. Methods Descriptive analysis of six national health surveys. Blood pressure was measured twice and the second record herein analysed. We defined four groups: i) people with self-reported hypertension diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“… 23 In Peru however, those unaware of their hypertension had the highest mean BP, followed by the treated, then those aware but not receiving treatment. 24 Treatment failure in our study could be explained by several patient‐related factors including poor adherence which might be related to side effects and local beliefs or misconceptions around hypertension, 25 , 26 , 27 or a lack of awareness of the serious risks to their future health. Medication adherence is a vital component to treatment success which has been previously evaluated in The Gambia and found to be sub‐optimal.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“… 23 In Peru however, those unaware of their hypertension had the highest mean BP, followed by the treated, then those aware but not receiving treatment. 24 Treatment failure in our study could be explained by several patient‐related factors including poor adherence which might be related to side effects and local beliefs or misconceptions around hypertension, 25 , 26 , 27 or a lack of awareness of the serious risks to their future health. Medication adherence is a vital component to treatment success which has been previously evaluated in The Gambia and found to be sub‐optimal.…”
Section: Discussionmentioning
confidence: 80%
“…A study of older persons (aged 60−69 years) in the United Kingdom found significantly higher BP levels among individuals receiving treatment compared to those not receiving treatment 23 . In Peru however, those unaware of their hypertension had the highest mean BP, followed by the treated, then those aware but not receiving treatment 24 . Treatment failure in our study could be explained by several patient‐related factors including poor adherence which might be related to side effects and local beliefs or misconceptions around hypertension, 25–27 or a lack of awareness of the serious risks to their future health.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Comparison of body mass index (BMI) from measurements with responses to questions about screening for diabetes can also highlight weaknesses in current diabetes screening programmes. (18) HES can identify under-diagnosis and can also monitor disease management, for example hypertension (19)(20)(21) and diabetes. (22) In Italy, in HES 2008-2012, direct measurement of blood pressure, cholesterol and glycaemia identified that 39% of men and 34% of adult women were unaware of their raised blood pressure; 38% and 42%, respectively, were unaware of probable hypercholesterolemia; and 39% and 29%, respectively, were unaware of probable diabetes.…”
Section: Agenda Settingmentioning
confidence: 99%
“…Research highlights the relationship between factors such as age and sex with the risk of suffering from CVD, indicating differences in susceptibility and disease patterns between various population groups (5,6). Furthermore, access to and coverage of health insurance emerge as crucial elements that directly impact the quality and outcomes of CVD treatment (7,8).…”
Section: Introductionmentioning
confidence: 99%